Standard specification for gray iron castings for elevated temperatures for non-pressure containing parts1. (American Society for Testing and Materials, 2006)
This specification covers three classes of gray iron suitable for castings exposed to temperatures encountered in such service as grate bars, stoker links, stoker parts, oil still furnace parts, firebox parts, ingot molds, glass molds, caustic pots, and metal melting pots.